Analytical approach for simultaneous determination of azoxystrobin, prothioconazole and trifloxystrobin in plant protection products - Lazić, Sanja; Šušnjar, Aleksandra; Vuković, Slavica; Ećimović, Jelena; Đukanović, Mitar; Šunjka, Dragana B (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2025)
IIn this study, an isocratic reversed-phase high-performance liquid chromatographic (RP-HPLC) method with diode array detection (DAD) was developed and validated for simultaneous determination of azoxystrobin, trifloxystrobin and prothioconazole in plant-protection products. Chromatographic separation of the active substances was achieved using 0.1% acetic acid and acetonitrile (30:70 v/v) at a flow rate of 0.52 ml/min on a Zorbax Eclipse XDB-C18 (50 mm × 4.6 mm × 1.8 μm) and UV detection at 210 nm. Validation was done by evaluating the linearity and precision of the method, repeatability of injections, accuracy, and limits of detection and quantification (LOD and LOQ). Under the conditions, correlation coefficients of linearity were 0.996-0.997, the precision of method, expressed as relative standard deviation, was lower than the modified Horwitz values, the accuracy of all individual substances was within the range of 94.61-107.35%, while repeatability of the injectons was satisfied with RSD of 0.94-1.35%. LOD and LOQ were 0.0063 mg/ml and 0.019 mg/ml for azoxystrobin, 0.0051 mg/ml and 0.015 mg/ml for prothioconazole and 0.0051 mg/ml and 0.015 mg/ml for trifloxystrobin, respectively. A simple, precise, accurate, and fast analytical method for simultaneous determination of the fungicides azoxystrobin, prothioconazole and trifloxystrobin can be proficiently used for their detection and quantification in formulated products. The developed and validated method was applied to real samples, confirming the method’s applicability.